Efficiency Of Shariah Invesment In the Maqshid Sharia Implementation - Zahwa, Muhammad Faisol (Universitas Syiah Kuala, 2024)
This study aims to discuss the efficiency of sharia investment in the implementation of maqashid sharia. In today's era of increasingly modern economic development, to avoid usury and regulations that are not in accordance with Islamic law, there is sharia investment. This study uses a qualitative method with a literature study. The results of this study show that Sharia investment has a meaning, namely, a system or processing of funds for the long term with a concept in accordance with Islamic law. The efficiency of sharia investment in maqashid sharia is the application of investment based on Islamic laws to avoid usury or various investment offers that do not meet Islamic law. Types of Sharia investment include stocks, Sharia mutual funds, Sharia deposits, Sharia bonds/sukuk, gold, property investment, and security crowdfunding (SCF). The implementation and utilization of sharia investment in the role of maqashid sharia aims to preserve religion, reason, soul, descendants, and property.